Do special constables in London feel that they are adequately prepared to meet their first aid responsibilities? A qualitative study. Issue 1 (29th January 2016) - Chandan, Joht Singh; Meakin, Richard
Abstract : Objective: This study's aims were to explore the views of special constables in the London metropolitan police force concerning their obligations and skills as first aiders. Background: The metropolitan police force provides police officers to act as first responders to emergency calls made by the public. Special constables act with the same powers and responsibility as police officers and are required to deal with incidents involving medical emergencies. Setting: West London Police Station. Participants: Fifteen special constables entered and completed the study. Methods and Outcome Measures: A qualitative study involving semistructured interviews, participant observation, and reflective work. The outcome measures were the themes derived from the 'thematic framework approach' to analysis. Results: Four main themes were identified. (1) 'Our responsibility?'—Special constables felt they had a responsibility, but were unsure of the origin of this responsibility, with many feeling it stemmed from public expectation. (2) 'Confidence'—Special constables had mixed feelings regarding their confidence in first aid scenarios and many felt that more could be done to improve their confidence. (3) 'Training needs'—Many felt the current training system was lacking in several ways including regularity, teaching and content. (4) 'Personal first aid knowledge'—Special constables were disappointed with their past performances. Conclusions: Owing to the small size of this study, the conclusions are limited; however, if the findings are confirmed by larger studies, they suggest the need to improve the confidence of special constables in first aid situations.